2004
DOI: 10.1080/14015430310021618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a consecutive group of transsexual individuals referred for vocal intervention in the west of Sweden

Abstract: Male-to-female transsexual individuals frequently experience difficulties in increasing the fundamental frequency so that they can pass as members of the preferred gender. Female-to-male individuals may also meet with vocal problems although hormone treatment lowers fundamental frequency. The purpose of this study was to explore the transsexual individuals who, as part of their reassignment process, were referred to the voice clinic at the Sahlgrenska University Hospital in Göteborg, Sweden, between 1991 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 14 publications
2
79
0
Order By: Relevance
“…Vocal pitch is a strong gender marker, 4 and male-to-female TS (M-F TS) individuals who are perceived as females generally have higher mean speaking fundamental frequency (SFF) than those perceived as males. 5,6 Thus, much focus has been on helping M-F TS clients achieve and maintain female pitch characteristics. Hormone supplements of estrogen have no known biological effect on the male larynx and do not help to raise the fundamental frequency (F 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vocal pitch is a strong gender marker, 4 and male-to-female TS (M-F TS) individuals who are perceived as females generally have higher mean speaking fundamental frequency (SFF) than those perceived as males. 5,6 Thus, much focus has been on helping M-F TS clients achieve and maintain female pitch characteristics. Hormone supplements of estrogen have no known biological effect on the male larynx and do not help to raise the fundamental frequency (F 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Dacakis 7 and Soderpalm et al 8 were milestones in that they provided acoustic data on short-and longterm outcomes of voice therapy for MTF TG individuals. However, neither study provided perceptual data to assess listener responses to the voice changes made by subjects.…”
Section: Introductionmentioning
confidence: 98%
“…According to Soderpalm et al, 8 each therapy session lasted for 45-60 minutes and comprised two parts: vocal hygiene exercises, including relaxation, breathing, and phonation balanced in expiratory and laryngeal muscular effort; and phonatory/articulatory exercises, including gradual pitch climbing, improving articulatory contacts, and encouraging anterior articulatory placement. It was noted that therapy was loosely based on the accent method.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, an MFT person is anatomically male; the larynx in males is typically larger, and the vocal folds are longer and more massive. 20,21 S€ oderpalm et al 11 reported endoscopic information regarding the larynx in MFT persons followed up for communication intervention. They indicated no structural differences of MFT individuals compared with nontranssexual males.…”
Section: Introductionmentioning
confidence: 98%
“…The dysphonia index scores from the three MFT participants who received voice treatment reflected a reduction in hyperfunctional voice production, whereas the index for the two untreated individuals indicated persistent hyperfunction at a level that was considered pathologic. Oates and Dacakis 1 and S€ oderpalm et al, 11 among others, have advocated voice therapy for MFT clients who are seeking to feminize their voices to prevent use of potentially abusive vocal behaviors. Despite the expressed concern about increased vocal hyperfunction in MFT persons, only a few descriptions of laryngeal behavior from visual observations are in the extant literature.…”
Section: Introductionmentioning
confidence: 99%